Dendrite‐Free Sodium Metal Anodes Enabled by a Sodium Benzenedithiolate‐Rich Protection Layer. Issue 16 (19th February 2020) - Zhu, Ming; Wang, Guanyao; Liu, Xing; Guo, Bingkun; Xu, Gang; Huang, Zhongyi; Wu, Minghong; Liu, Hua‐Kun; Dou, Shi‐Xue; Wu, Chao
Abstract: Sodium metal is an ideal anode material for metal rechargeable batteries, owing to its high theoretical capacity (1166 mAh g −1 ), low cost, and earth‐abundance. However, the dendritic growth upon Na plating, stemming from unstable solid electrolyte interphase (SEI) film, is a major and most notable problem. Here, a sodium benzenedithiolate (PhS2 Na2 )‐rich protection layer is synthesized in situ on sodium by a facile method that effectively prevents dendrite growth in the carbonate electrolyte, leading to stabilized sodium metal electrodeposition for 400 cycles (800 h) of repeated plating/stripping at a current density of 1 mA cm −2 . The organic salt, PhS2 Na2, is found to be a critical component in the protection layer. This finding opens up a new and promising avenue, based on organic sodium slats, to stabilize sodium metals with a protection layer. Abstract : A sodium benzenedithiolate (PhS2 Na2 )‐rich protection layer synthesized in situ on sodium by a facile method effectively prevents dendrite growth in carbonate electrolyte, leading to stabilized sodium metal electrodeposition for 400 cycles (800 h) of repeated plating/stripping at a current density of 1 mA cm −2 .